he development of unablauted *ęT in locality names and topographic names in Western Pomerania (Poland) and the evolution of *ęT in Lechitic languages and dialects and in Lower Sorbian (cf. Kashubian v'izc, v'izą, v'ize and v'ǫzc, v'ąze 'knit, tie' and Low - Duma, Jerzy (Papers in Linguistics, 2019)
The proto-Lechitic ablaut *ęT > *'ǫT, as in Kashubian v'ǫzc, v'ąze in opposition to the regular unchanged form v'izc, v'ize did not occur in some preserved Slavic place names in the southern area of Western Pomerania: from the area south of Szczecin into regions of Darłowo in Middle Pomerania, e.g. Kotentowe - Chociętowo, Diosintablotta :*desęt- 'ten'. In this area the absence of *ŕ̥T > *r̥T umlaut is also noted, e.g. Czirnowe : czarny 'black', Dirloua 'Darłowo'. The absence could have been caused by some early contacts with a Slavic population from the Sorabian group, in which Proto-Lechitic umlaut *ęT > *'ǫT did not occur.